Rimsko dominantno število - Repolusk, Polona (Obzornik za matematiko in fiziko, 2013)
We present a concept of the domination and the Roman domination based on motivation from everyday life. We focus our attention to the roman domination and present some basic properties of this graph invariant. Using these properties we determine the exact values of the Roman domination number of some special graph classes.
Keywords: graph theory; teorija grafov; rimska dominacija; Roman domination number; Roman domination finction; rimska dominantna funkcija; rimsko dominantno število; Roman graph; rimski graf